New records of phytoplankton for Bangladesh. 5. Euglena, Euglenocapsa - Khondker, Moniruzzaman; Bhuiyan, Rauf Ahmed; Yeasmin, Jenat; Alam, Munirul; Sack, R. Bradley; Huq, Anwar; Colwell, Rita R. (Bangladesh Journal of Plant Taxonomy, 2008)
This study presents 20 taxa of the genus Euglena and one species of the rare euglenoid genus Euglenocapsa. All these taxa are reported for the first time from some pond ecosystems of Mathbaria in Pirojpur and Bakerganj of Barisal districts of Bangladesh. Keywords: Phytoplankton, New records, Bangladesh, Euglena, Euglenocapsa, Ponds DOI: 10.3329/bjpt.v15i1.910 Bangladesh J. Plant Taxon. 15(1): 39-46, 2008 (June)